The adenovirus type 2 DNA-binding protein interacts with the major late promoter attenuated RNA. - Seiberg, M (1989)
The adenovirus 72-kilodalton DNA-binding protein (DBP) binds to the attenuated RNA derived from the viral major late promoter. Protection from T1 RNase digestion can be observed when DBP is incubated with attenuated RNA. By using attenuated RNA labeled at one end, the T1 RNase digestion pattern can be mapped to residues located at specific sites in this RNA. Heterologous competitor RNAs do not alter the pattern of DBP protection of a labeled attenuated RNA, as does the identical attenuated RNA. These data indicate some specificity of the interaction between DBP and attenuated RNA. Adenovirus infection of monkey cells results in a more efficient attenuation of RNA initiated at the major late promoter and a reduced level of infectious virus. Adenovirus mutations in DBP relieve this restriction. These DBP mutant proteins do not change their binding properties to the attenuated RNA but suggest a mechanism by which DBP plays a role in the adenovirus host range restriction in monkey cells.